Ship movements' analysis in a scale model - Simão, J. (2016)
A set of physical model tests was run in order to characterize the ship’s response to different wave conditions going from frequently-occurring conditions up to extreme ones. Several wave heights, periods and directions were generated. The waves around the ship were measured with probes and the movements of the ship were measured with a fiber-optic gyrocompass. Transfer functions are established and compared with numerical ones obtained with the WAMIT model.